Electrochemical Cross‐Dehydrogenative Coupling of N‐Aryl‐tetrahydroisoquinolines with Phosphites and Indole. Issue 14 (26th March 2019) - Xie, Wenxia; Liu, Nian; Gong, Bowen; Ning, Shulin; Che, Xin; Cui, Lili; Xiang, Jinbao
Abstract : A metal‐ and reagent‐free, electrochemical cross‐dehydrogenative coupling reaction of N ‐aryl‐tetrahydroisoquinolines with phosphites and indole is developed. This method provides an environmentally benign and simple approach for the construction of C–P and C–C bonds in moderate to high yields with wide tolerance of functional groups. Abstract : A metal‐ and reagent‐free, electrochemical cross‐dehydrogenative coupling reaction of N ‐aryl‐tetrahydroisoquinolines with phosphites and indole was reported, providing an environmentally benign and simple approach for the construction of C–P and C–C.